2000
DOI: 10.1046/j.1365-2559.2000.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Ber EP4 and epithelial membrane antigen aid distinction of basal cell, squamous cell and basosquamous carcinomas of the skin

Abstract: Distinction of basal and squamous cell carcinomas of the skin can be readily achieved with routine immunohistochemistry using Ber EP4 and EMA. Identification of basosquamous carcinoma is also facilitated with this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
114
4
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 22 publications
(52 reference statements)
15
114
4
7
Order By: Relevance
“…34 The utility of this antibody in distinguishing basal cell carcinoma and squamous cell carcinoma based upon its consistent expression in the former and absence in the latter is well documented. 35,36 While we also found BerEP4 in all cases of infiltrative basal cell carcinoma in our study, we noted strong BerEP4 expression in 38% our microcystic adnexal carcinoma cases. Similar to our study, Smith et al 23 reported BerEP4 immunoreactivity in glandular areas of their 10 cases of microcystic adnexal carcinoma.…”
Section: Discussionsupporting
confidence: 52%
“…34 The utility of this antibody in distinguishing basal cell carcinoma and squamous cell carcinoma based upon its consistent expression in the former and absence in the latter is well documented. 35,36 While we also found BerEP4 in all cases of infiltrative basal cell carcinoma in our study, we noted strong BerEP4 expression in 38% our microcystic adnexal carcinoma cases. Similar to our study, Smith et al 23 reported BerEP4 immunoreactivity in glandular areas of their 10 cases of microcystic adnexal carcinoma.…”
Section: Discussionsupporting
confidence: 52%
“…It is well known that the expression of EMA is uncommon in BCCs (28,29), which corroborates the results of our present study.…”
Section: -------------------------------------------------Class III ßsupporting
confidence: 93%
“…Ber-EP4 has been proven to be negative in peripheral ameloblastomas [11,12]. Additionally, epithelial membrane antigen (EMA) a mucinlike glycoprotein often used as a pan-epithelial marker has been utilized to differentiate BCC from SCC, especially since some variants of SCC such as basaloid SCC may resemble BCC [13,14].…”
Section: Discussionmentioning
confidence: 99%